Seroprevalence and factors associated with surface antigen of Hepatitis B virus and anti Hepatitis C virus antibody among southern region of India, Tamil Nadu - Krishnasamy, Narayanasamy; Rajendran, Karthick; Radhakrishnan, Parvathavarthini; Annasamy, Chezhian; Ramalingam, Senthilkumar (International Journal of Infection Control, 2015)
Hepatitis B and C are emerging viral infections, leading cause of liver cirrhosis and hepatocellular carcinoma with particular relevance in liver transplantation around the world. Though several studies from different countries have estimated the prevalence of this viral infection, few studies only exists in Indian population. Our specific aim is to find out the prevalence and predicting factors of the HBV and HCV infections in urban, suburban, rural, tribal populations in southern region of India. Study was conducted from different areas of southern region and blood was collected along with questionnaires from all participants for serological analysis of HBV and HCV. The prevalence of HBV infection in the population was 3.3%, and HCV infection was 0.3% and prevalence rate of HBV infection was urban (4.5%), suburban (1.6%), rural (3.2%), tribal (0%). Incidentally, this is the first report from southern region of India in a large scale with clear area wise prevalence rate of infection. The multinomial logistic regression analysis showed that the risk of HBV infection was greater for gender (OR- 0.589, 95% CI- 0.363 to 0.955, P = 0.032), place of living (OR- 0.702, 95% CI- 0.536 to 0.920 P = 0.010), marital status (OR- 2.783, 95% CI-1.130 - 6.853, P = 0.026) and occupation (OR- 0.789, 95% CI- 0.657 to 0.948, P = 0.011). Epidemiology of HBV and HCV infections were in this southern region evidently elucidated that low prevalence for hepatitis C virus and slightly high prevalence for hepatitis B virus with higher rates in urban areas than other Northern regions of India.